A Novel KDF1 Variant is Associated With Multiple Natal Teeth, Tooth Agenesis, and Root Maldevelopment - John M. Graham, Jr.; Pedro A. Sanchez-Lara; Atsushi Ohazama; Katsushige Kawasaki; Stefan T. Arold; Piranit Nik Kantaputra (International Dental Journal)
Objective: Natal teeth are teeth that are present at birth. Multiple natal teeth are extremely rare. The objective of this study was to find the molecular aetiology of a unique dental phenotype including natal teeth, tooth agenesis, and root maldevelopment in a 5-generation family. Methods: Oral and radiographic examination, linkage analysis, whole genome sequencing, and an immunohistochemical study of Kdf1 during tooth development in the mouse embryo were performed. A protein model was generated. Results: We report a 5-generation family in which multiple natal teeth, oligodontia, and root maldevelopment manifested with autosomal dominant inheritance. Linkage analysis and whole genome sequencing revealed a novel pathogenic variant c.845T>G; p.Ile282Ser, which cosegregated in 9 affected and 10 unaffected family members. This amino acid Ile282 is highly conserved and is important for the stabilization of a small helical fragment. This stabilization is lost in the Ile282Ser mutant, resulting in disruption of the interaction of KDF1 with its partner proteins, including IKKA, which are important for epidermal proliferation and differentiation and subsequent tooth development. Conclusions: Our study demonstrates for the first time that natal teeth, tooth agenesis, and root maldevelopment are caused by a KDF1 variant. Our study highlights the important role of KDF1 in tooth formation and eruption.